Recurrent Ethmoidal Polypi: A Prospective Study - M. Musharaf Baig ,Tahir Hussain (Journal of Rawalpindi Medical College, 2008)
Background: To evaluate the various aspects of recurrent ethmoidal polypi and to ascertain the treatment modality with the least recurrence, Method: The study was conducted on 110 patients over a two year period (February 2003 to January 2005). All presented in the OPD of Holy Family Hospital Rawalpindi with recurrent ethmoidal polypi. A proforma was allocated to every patient to record, present and past history of the disease, H/O allergy, upper respiratory tract infections and family history. Previous treatment modalities either medical or surgical and number of recurrences were noted. Thorough ENT examination and relevant investigations were carried out. Results: There was predominance of male (68%) and adult patients (70%). Most of the patients presented in winter season, with nasal obstruction (87%), rhinorrhoea (81%), PND (49%) sneezing (43%) and headache (42%). Previously patients had undergone conservative treatment in 25% and simple polypectomies in 64%. Case recurrence was treated with medical treatment (anti histamines and topical steroids), with 52.7% success. Repeated polypectomy followed by topical steroids was successful in 60%. 4 patients required external ethmoidectomy followed by antihistamines with 100% results. Conclusion: In most of the patients recurrence of polypi can be treated by medication and meticulously performed simple polypectomy followed by antihistamines and or local steroids. About 5 to 10 percent patients require extensive surgical operations. External ethmoidectomy is the final court of appeal with 100% results.